2008
DOI: 10.1021/jf8023134
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of Prometryne in Soil As Affected by Dissolved Organic Matter

Abstract: Incorporation of organic fertilizers/amendments in soils has been, and will continue to be, a popular strategy for improving the quality of arable soils. However, the mechanism by which the dissolved organic matters (DOMs) affect soil properties or interact with other substances in soils is largely unknown. In this study, a batch equilibrium experiment was performed to evaluate the effect of two types of DOMs on the behavior of prometryne (a herbicide) in soils. Two sorts of DOMs were derived from lakebed slud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 47 publications
2
37
0
1
Order By: Relevance
“…However, addition of exogenous DOC at the finial equilibrium concentration of 100 mg/L significantly reduced the adsorption capacity of the soil for TBBPA (12% reduction in the K f value, Table 4). DOC at high concentrations may compete for the adsorption sites in the soils, therefore inhibiting TBBPA adsorption [22]. This result suggested that transportation of TBBPA may be facilitated with the presence of high DOC in the real and complicated environment.…”
Section: Adsorption Of Tbbpa On Various Soil Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, addition of exogenous DOC at the finial equilibrium concentration of 100 mg/L significantly reduced the adsorption capacity of the soil for TBBPA (12% reduction in the K f value, Table 4). DOC at high concentrations may compete for the adsorption sites in the soils, therefore inhibiting TBBPA adsorption [22]. This result suggested that transportation of TBBPA may be facilitated with the presence of high DOC in the real and complicated environment.…”
Section: Adsorption Of Tbbpa On Various Soil Componentsmentioning
confidence: 99%
“…Peat was mixed with 0.01 M CaCl2 (solid: solution 1:10 (w:v)) and the suspension was shaken for a month. After centrifugation, the supernatant was filtered through 0.45 m membrane and the filtrate was collected DOC-added [22] using Pearson's correlation analysis and multiple linear regression analysis by SPSS 14.0.…”
Section: Treatmentmentioning
confidence: 99%
“…2b), suggesting that DOM was able to affect fluroxypyr dissipation. It was possible that DOM modulated microbial activities through their active organic fractions (Said-Pullicino and Gigliotti 2007;Jiang et al 2008;Song et al 2008). Therefore, addition of DOM to soils could facilitate the decay of fluroxypyr.…”
Section: Effect Of Dom On Fluroxypyr Degradation In Soilsmentioning
confidence: 99%
“…This herbicide is mainly applied for weed control, however the application does not ensure that it is safe for main crop such as sugarcane, maize etc. It was also true that very less amount is utilized by the targeted plants and major portion is retained in the soil itself (Jiang et al 2008). As a result, during the heavy rainfall the residues present in the soil can easily enter into the water body and thereby causing water pollution.…”
Section: Introductionmentioning
confidence: 99%